Иуда Искариот - Андреев Леонид Николаевич (Шедевры мировой классики, 2015)
Экземпляры: ф.6 (20190729) / Инвентарный номер: 2847 И / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: А 65 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)1-44